(untitled) (La U Investiga, 2017)
Treatment of cervical cancer in locally advanced stages is based primarily on ionizing radiation therapy and radiosensitizing chemotherapy. This type of therapy has among its most serious and morbid adverse effects, the generation of vaginal fistulas. It is important to establish the punctual prevalence of this adverse effect in our environment as well as to establish the risk factors for the generation of fistulas associated with the treatment. An observational, retrospective, study was conducting. Patients who received external radiotherapy 2D or 3D mode plus brachytherapy or external boost were enrolling, with or without concurrent chemotherapy. The specific prevalences of fistulas were obtein for each case and the respective association with the controls was make using the Odds Ratio. The punctual prevalence of fistulas in our center was 2.93%, 1.62% were under conventional radiotherapy and 1.31% conformational, 1.62% patients who received concurrence and 1.31% who did exclusive radiotherapy. The proportion of fistulas was 50% for external boost, 33% for brachytherapy and 17% without boost or brachytherapy. The external boost vs. brachytherapy showed an OR = 4.77 95% CI (1.66 - 13.65). The prevalence of fistulas in our center is in accordance with the world reality; however, the association of external radiotherapy boost with more fistulas vs brachytherapy reinforcement shows the importance of bringing the largest number of patients to brachytherapy.